Disseminated Cryptococcus neoformans infection associated to COVID-19 - Diana Alegre-González (Elsevier, 2021)
Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is a novel coronavirus associated with immune dysregulation. The use of immunosuppressant drugs as part of COVID-19 treatment (such as Tocilizumab or high -dose corticosteroids) increases the risk of opportunistic infections. Here we present a case of a patient without prior immunosuppression that developed a serious fungal infection after the use of high dose corticosteroids in the setting of severe COVID-19 and cryptogenic organizing pneumonia.